Effectiveness Test of The Use of Nigella Sativa Oil Compared with Sodium Docusate as A Therapy for Cerumen Impaction on Children at Puteri Aisyiyah Medan Orphanage in Vitro - Siregar, Anandya Annisa Amri; Syahputra Nasution, Muhammad Edy (Buletin Farmatera, 2024)
Abstract: Introduction: Cerumen Impaction is a hearing problem that most often results in decreased hearing function and ear pain. Treatment using natural ingredients is widely practised. One of them is the use of Nigella sativa Oil. The purpose of this study was to analyze the effectiveness of using Nigella sativa Oil and sodium docusate as a treatment for impaction of cerumen in children at the Puteri Aisyiyah Orphanage in Medan City in vitro at 5,10,15and 30 minutes. This type of research was a eksperimental study in vitro which in practice uses a probability sampling technique, namely simple random sampling on existing groups. Significance value of 0.000(p 0.05).So it can be stated that the use of the Nigella Sativa Oil solution and the Docusate Sodium solution have different effectiveness, while this difference can be seen from the Mean ± Deviation Standard value in each group, where the Nigella Sativa Oil solution has a higher Mean ± Deviation Standard value (0.788 ± 0.144) compared to sodium docusate solution (0.145 ± 0.125). The conclusion is that the use of Nigella Sativa Oil has significant effectiveness for the treatment of impaction of cerumen and the use of Sodium Docusate does not have significant effectiveness for the treatment of impaction of cerumen in children.